2010
DOI: 10.1080/13548501003623963
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs underlying UK parents' views towards MMR promotion interventions: A qualitative study

Abstract: This study sought to extract underlying beliefs towards measles, mumps and rubella (MMR) vaccination from UK parents' views towards potential motivational and organisational interventions to boost MMR vaccination. Thematic analysis of transcripts of five focus groups identified five underlying psychological themes: parents' information needs, distrust of government sources, trust of other parents, attentional biases towards risk information and problems of achieving ''balance'' in MMR information provision. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 17 publications
1
55
0
Order By: Relevance
“…A few studies also reported beliefs that the diseases prevented by the MMR vaccine are mild, treatable, and not dangerous [135,138,140,142] and that children actually benefit from these infections [134,141,142]. Mistrust of governments was high [135,137,139], together with perceptions that doctors are dismissive of parents safety concerns [133,137,142].…”
Section: Mmr Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies also reported beliefs that the diseases prevented by the MMR vaccine are mild, treatable, and not dangerous [135,138,140,142] and that children actually benefit from these infections [134,141,142]. Mistrust of governments was high [135,137,139], together with perceptions that doctors are dismissive of parents safety concerns [133,137,142].…”
Section: Mmr Vaccinesmentioning
confidence: 99%
“…Twelve articles studied MMR vaccination [132][133][134][135][136][137][138][139][140][141][142] and found that the most important concerns were about safety, with some articles reporting particular worries about autism [132,134,136-1 38,140,141]. A few studies also reported beliefs that the diseases prevented by the MMR vaccine are mild, treatable, and not dangerous [135,138,140,142] and that children actually benefit from these infections [134,141,142].…”
Section: Mmr Vaccinesmentioning
confidence: 99%
“…First, results may be confounded by vaccination acceptability. We chose to focus scenarios on influenza vaccination because we assumed that it would minimize the risk of results being influenced by negative parental attitudes towards the vaccine, as have been documented towards the MMR vaccine (Gardner et al, 2010). Yet, parental resistance to vaccination more broadly has been documented in the UK and other European countries (Blume, 2006), and even parents that choose to vaccinate may worry about vaccine safety and side effects (Harvey, Good, Mason, and Reissland, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Weinstein, 1987), and that parents may be highly sensitive to risk when making healthrelated decisions for their children (e.g. Gardner, Davies, McAteer and Michie, 2010). Work on vaccination acceptance, in which two potential risks are present -disease risks associated with rejecting a vaccine, and possible complications arising from accepting a vaccine -has found that parents pay more attention to unlikely high-risk consequences than the likely benefits, despite acknowledgement of the low probability of aversive consequences being realized (Gardner et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation